Prognostic Role of Tumour Stroma Ratio in Oral Squamous Cell Carcinoma Arising in the Background of Oral Submucous Fibrosis: A Retrospective Study - Pradeep Veerappan; Reshma Poothakulath Krishnan; Deepak Pandiar; Pratibha Ramani; Selvaraj Jayaraman (Journal of Clinical and Diagnostic Research)
Introduction: Oral Submucous Fibrosis (OSMF) is a potentially malignant disorder with an increased risk of malignant transformation. Oral Squamous Cell Carcinoma (OSCC) arising in the background of OSMF shows distinct clinical presentation and behaviour. The present study was done with the rationale to understand the disease progression and assist in treatment planning using Tumour Stroma Ratio (TSR). Aim: This study aimed to evaluate the role of TSR in OSCC arising in the background of OSMF. Materials and Methods: This retrospective study was conducted in the Department of Oral Pathology and Microbiology, Saveetha Dental College and Hospitals, Chennai, Tamil Nadu from January 2024 to June 2024. Only patients reported with conventional OSCC with detailed clinicopathological and survival data were included in this study. A total of 120 slides were retracted from the departmental records and grouped into Group-1- OSCC arising in the background of OSMF (30 cases), Group-2- Well Differentiated OSCC (WDSCC) (30 cases), Group-3- Moderately Differentiated OSCC (MDSCC) (30 cases), and Group-4- Poorly Differentiated OSCC (PDSCC) (30 cases). Group-2, 3 and 4 cases showed no clinical signs or histopathological features of OSMF. The TSR was evaluated at the invasive front of the tumour and recorded as stroma-high and stroma-low. The survival data for these patients were retrieved from the medical records. Kappa statistics, Chi-square and Kaplan-Meier survival analysis were performed to statistically analyse the results. A p-value of ≤0.05 was considered statistically significant. Results: A total of 26 (86.6%) cases of OSCC arising in the background of OSMF showed stroma-low and 4 (13.3%) cases showed stroma-high TSR. The WDSCC group exhibited a predominance of stroma-low tumours with 24 cases (80%) of stroma-low and six cases (20%) of stroma-high TSR. In MDSCC group, 20 cases (66.6%) showed stroma-low and 10 (33.3%) cases showed stroma-high TSR. Notably, the PDSCC group had a significantly higher proportion of stroma-high tumours, with four cases (13.3%) of stroma-low and 26 cases (86.6%) of stroma-high TSR. This difference between the four groups was statistically significant (p<0.001). On survival analysis, it was noted that the stroma-low cases had a better survival rate than stroma-high TSR. Conclusion: OSCC arising in the background of OSMF are low-grade tumours and TSR can be helpful in predicting the survival rate of OSCC patients.